Papel da proteína Fbxo7 no perfil de citocinas produzidas em linhagem celular monocítica humana (THP-1) estimulada por lipopolissacarídeo - Martins, Isabela Fernanda Morales (2021)
The canonical function of SCF E3 ubiquitin ligase complexes is the ubiquitination of their substrates, directing them to proteasomal degradation or modulation of function. From these complexes, F-box protein class is the most important component due to their substrate recognition, which ensures the specificity of the complex. In 2012, it was described that Fbxo7 acts as a negative regulator in the nuclear transcription factor kappa B (NF-kB) signaling pathway in human osteosarcoma cell line (U2OS). This pathway is regulated by several ubiquitination events, thus being responsible for regulating inflammation via activation of genes involved in the immune response, including cytokines. So far it has not been evaluated whether Fbxo7 can regulate the cytokine profile through NF-kB. Therefore, the aim of this work was to investigate the role of Fbxo7 in cytokine production using THP-1 cells stimulated by lipopolysaccharide (LPS). Since macrophages help to direct the standard immune response through cytokines, we used the differentiated THP-1 lineage for this study. We performed FBXO7 knockdown by specific siRNA in these cells and stimulated the NF-kB pathway with LPS, followed by the evaluation of 36 cytokines through an array containing capture antibodies for each cytokine. We verified a reduction in the amount of CCL1, CCL3, IL-10 and IL-1β in FBXO7 knockdown cells when compared to the control. Considering that IL-1β is a potent pro-inflammatory cytokine and is produced mostly by macrophages, we also evaluated the expression of the IL-1β gene by RT-qPCR. We noticed that, although there was a reduction in the protein level of IL-1β, there was an increase in transcription of this gene, which may suggest that cells are trying to compensate the reduction in protein levels by increasing gene expression. In addition, we did not find any change in the transcription of NF-kB after the knockdown of FBXO7. Considering that IL-1β is post-translationally regulated, we suggest a regulatory mechanism of Fbxo7 for IL-1β secretion by LPS-stimulated, differentiated THP-1 cells. Thus, this work contributed for the understanding of the role of another F-box protein in the immune response.